A hybrid Pythagorean fuzzy AHP - CoCoSo framework to rank the performance outcomes of circular supply chain due to adoption of its enablers - Lahane, Swapnil (Waste management (New York, N.Y.), 2021)
Copyright © 2021 Elsevier Ltd. All rights reserved.